Resolução de problemas matemáticos modelados com funções quadráticas utilizando os pilares do pensamento computacional no Ensino Médio - Veiga, Juliana Rodrigues da (2023)
This dissertation is part of the research line Information, Communication and Interaction Technologies, applied to Science and Mathematics Teaching and its general objective is to develop a didactic sequence for learning the relationships between two variable quantities depending on the 2nd grade, based on use of computer programming with 1st grade high school students. The research problem presents the following guiding question: how does the use of Computational Thinking contribute to the understanding of the relationships between two variable quantities present in the study of 2nd grade functions, for 1st grade high school students? To help achieve the general objective, the following specific objectives were outlined: a) explore the pillars of Computational Thinking for solving mathematical problems; b) understand the relationship between variable quantities when solving problems involving computer programming language; c) identify variable quantities present in mathematical problems using computer programming. A broad referential research was necessary in order to conceptualize the terms present in the text, such as Digital Information and Communication Technologies, Network Technologies, Computational Thinking and its pillars, algebra and the relationship between variable quantities. During this research, an educational product was created in the form of a didactic sequence, structured in seven meetings, applied to a 1st Grade High School class, made up of 19 students, from a private school, based in the municipality of Campos. New in Santa Catarina. The bibliography adopted for the methodological path of the didactic sequence was Constructionism, for expanding the possibilities of the computer in education and the use of block programming with Scratch. The research methodology predominantly adopts qualitative methods, with observations, recordings and logbooks as data collection instruments. The results obtained through the application of the educational product and the adopted analysis categories indicate an improvement in student engagement, as well as the use of techniques associated with the pillars of Computational Thinking for problem solving. Computational Thinking can help develop skills related to critical thinking and problem solving, and can also make the understanding of mathematical content more interactive and dynamic, allowing students to better understand the relationships between variable quantities. The Educational Product, in the form of a didactic sequence, which accompanies this dissertation, is available as support material for Basic Education teachers on the program website and on the EduCapes Portal http://educapes.capes.gov.br/handle/capes/ 743442.